Beyond the illness: a qualitative exploration of the burden of caring for people with tuberculosis on caregivers and their households in South Africa - Lieve Vanleeuw; Salla Atkins; Nasiphi Gwiji; Namhla Sicwebu; Wanga Zembe-Mkabile (Global Public Health)
Tuberculosis (TB) affects not only the person sick with TB but also their households. Our study aimed for a deeper understanding of the multiplicative impact of TB on households, and more specifically on caregivers of people with TB, as well as factors that influence the burden on caregivers in South Africa. We conducted an exploratory qualitative study focusing on the lived experiences of people providing care to a family member sick with TB. The study found that the burden of caregiving is significant and falls disproportionally on women and poorer households whose resilience has already been compromised by pre-existing multiple stressors and demands, contributing to health inequities and gender inequalities. Having to care for a household member sick with TB imposed an additional strain causing further health, financial and social problems, leaving the household in a worse-off position, and at a higher risk of continued ill health and further poverty. Social support was found to mediate the burden, however, was lacking for many as kinship bonds are weakened by high levels of poverty and unemployment. Support to households is recommended to ensure recovery of the person with TB and their household post-TB illness, and prevent further ill health and poverty.